2020
DOI: 10.1007/s00405-020-06396-8
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngological manifestations of hospitalised patients with confirmed COVID-19 infection

Abstract: The aim of our study is to evaluate the incidence and characteristics of otolaryngology symptoms in COVID 19 patients. Methods 116 patients with positive PCR test results for COVID-19 and followed up by otolaryngologists at a tertiary referral center/COVID-19 pandemic hospital were questioned in terms of otolaryngology symptoms associated with COVID-19 infection. Data including demographics, disease severity, concomitant diseases, previous otolaryngologic diseases,incidence and duration of new onset symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 34 publications
4
94
1
4
Order By: Relevance
“…Coronavirus-related otoneurological symptoms, such as tinnitus and balance disorders, have been described so far [ 10 , 23 29 ], as neurotrophic and neuroinvasive capabilities are typical of some coronaviruses [ 30 ]. Previous studies on other coronavirus infections showed a brain involvement, focusing attention on the possible neuro-auditory impairment following this infection [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronavirus-related otoneurological symptoms, such as tinnitus and balance disorders, have been described so far [ 10 , 23 29 ], as neurotrophic and neuroinvasive capabilities are typical of some coronaviruses [ 30 ]. Previous studies on other coronavirus infections showed a brain involvement, focusing attention on the possible neuro-auditory impairment following this infection [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing amount of scientific literature on COVID-19, studies that correlate audiovestibular symptoms to SARS-CoV-2 infection are still limited and further investigation is necessary for a better estimate of their incidence [ 10 , 23 29 ]. Furthermore, the incidence of audiovestibular symptoms among patients infected with other types of coronavirus (i.e., MERS and SARS) is debated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight cases developed sudden and complete loss of smell without respiratory symptoms (Gilani et al, 2020 ). Additionally, patients may present with other sensory dysfunctions, including oropharyngeal and ontological/vestibular disturbances: sore throat, dysphagia, vertigo, tinnitus, and hearing loss are common complications (Krajewska et al, 2020 ; Ozcelik Korkmaz et al, 2020 ). For instance, a middle-aged woman with sudden dizziness and dry throat was confirmed to have COVID-19.…”
Section: Neurological Complications Of Covid-19mentioning
confidence: 99%
“…Our approach differs from other reports that characterized patients which were already confirmed to have COVID-19. We aimed in our case series to investigate the occurrence of unidentified cases among ENT patients due to the overlap of common symptoms such as sore throat and nasal congestion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%